Revisiting the Role of Governance and Institutions in the Impact of Financial Liberalization on Economic Growth using the PSTR Model - Saidi, Hichem; Rachdi, Houssem; Mgadmi, Nidhal (Panoeconomicus, 2017)
This paper provides a comprehensive review of the literature on the dual effect of financial liberalization over more than three decades, starting from the independent contributions of Ronald I. McKinnon and Edwards S. Shaw on this topic. In this regard, the paper revisits the effects of financial liberalization and governance on growth. Moreover, it presents a summary of current research in this area, covering the conclusions of the endogenous growth models, issues on volatility and the relationship between financial liberalization, institutions, governance and economic growth. To study data of 54 countries from 1985 to 2010 and because the nexus between financial liberalization and economic growth is nonlinear and depends on specific national factors especially institutions quality and governance, the Panel Smooth Transition Regression (PSTR) model is used. The main result of this study shows that a better contribution of financial liberalization to economic growth requires the interrelationship and the complementarity between financial liberalization and governance. Overall, regardless of the level of liberalization, output income is always higher with better governance and institutions. Key words: Economic growth, Financial liberalisation, Institutions quality and governance, PSTR. JEL: E44, F36, G21, G28. Rad daje sveobuhvatan pregled literature o dvojnom efektu finansijske liberalizacije tokom više od tri decenije, počevši od nezavisnih doprinosa Ronalda I. McKinnona i Edvards S. Shav na ovu temu. U tom smislu, u radu se ponovo ispituje efekata finansijske liberalizacije i upravljanja na rast. Osim toga, rad predstavlja pregled trenutnih istraživanja u ovoj oblasti, prikazuje zaključke endogenih modela rasta, pitanja o nestabilnosti i odnos između finansijske liberalizacije, institucija, upravljanja i ekonomskog rasta. Kako bi se proučili podaci o 54 zemalja od 1985. do 2010. godine i zato što je veza između finansijske liberalizacije i ekonomskog rasta nelinearna i zavisi od specifičnih nacionalnih faktora, posebno kvaliteta institucija i upravljanja, koristi se Panel Smooth Transition Regression (PSTR) model. Glavni rezultat ovog istraživanja pokazuju da bolji uticaj finansijske liberalizacije na ekonomski rast zahteva međuzavisnost i komplementarnost između finansijske liberalizacije i upravljanja. Sve u svemu, bez obzira na nivo liberalizacije, prihod je uvek veći u slučaju boljeg upravljanja i institucija. Ključne reči: Ekonomski rast, Finansijska liberalizacija, Kvalitet i upravljanje institucijama, PSTR.